Relations of Human Rights Documentations with Constitutional Regulation of Rights - Badr Mohammed Taher Mustafa; Hawre Kamal Muhammed (QALAAI ZANIST JOURNAL, 2020)
Human right is an old subject, and an endeavor to achieve it has an old historical root. Human beings in their early existence and in early human community, endeavored to achieve their rights and freedom, and this endeavor still continues. The effect of these endeavors led to the upspring of a group of national documents about human rights in their countries. In the first half of twentieth century, humanity set the base of human rights through declarations and international agreements, and humanity get benefit from these rights now. Later, constitutions of countries which have the highest status in the countries, under the effect of these documents, national documents in particular, contained the subject of rights and freedom with regulation of the ways of governing the country. constitutional regulation of rights and freedom is mentioned differently in comparative constitutions.